Análise dos fatores de sucesso e insucesso do desmame da ventilação em pacientes vítimas de traumatismo crânio encefálico - Silva, Aliana Alves da (2020)
Introduction: traumatic brain injury (TBI) is an injury that compromises the extra or intracranial region. It is known that many patients have satisfactory evolution after their entry into the ICU, although some have failed in the weaning process. Objectives: To analyze the clinical profile and factors of success and failure of ventilatory weaning in patients with cranioencephalic trauma. Methodology: This is a descriptive, retrospective, and quantitative study that occurred in the period from April to June of 2017, at the José Frota - IJF Doctoral Institute. Results: We evaluated 17 patients, 15 of whom were males aged 17 to 65 years, the main cause of traffic accident. 70.6% required surgical treatment and only 2 patients had brain death. Of the 17 patients, only 1 presented atelectasis on the 7th day and 2 presented pneumothorax on the 1st day of hospitalization. With respect to hypersecretive patients, they were found in a higher percentage in the 1st and the 14th day. Pulmonary auscultations were found with the presence of snores and most of them with mucopurulent secretion. The ventilatory modes on day 1, day 7 and day 14 were mostly in A / C. The leukogram ranged from 6,690 to 19,530 cells / mm³ and the number of weaning attempts was maximum 3. Conclusion: Factors such as respiratory complications, the degree of brain damage and the presence of infections may influence the patient's clinical improvement and consequently the success or weaning failure.